Short-term stress from high light and high temperature triggers transcriptomic changes in the local lesions 1 rice mutant - Qiu, Zhennan (Plant Signal Behav, 2019)
High light and high temperature (HLHT) stress induces the production of damaging reactive oxygen species (ROS) in many plants. Recently, we described a HLHT-sensitive rice (Oryza sativa) mutant, local lesions (ls1), that exhibits local lesions under HLHT, due to DNA damage and excess ROS accumulation. Here, we determined that an HLHT treatment induced the local lesion phenotype in ls1 within 6 h. Corroborating this result, we found that transient HLHT treatment influenced the expression of many genes in the ls1 mutant, while affecting the growth and development of young leaves.